2013
DOI: 10.1111/jtsb.12039
|View full text |Cite
|
Sign up to set email alerts
|

The Theory of Conditionality: An Illustration of the Place of Norms in the Field of Social Thinking

Abstract: In the field of the central core theory of social representations, research which has focused on the normative aspects is relatively recent as it dates back little more than ten years. The theory of conditionality which developed from research into the periphery of representation results from this. It is a particularly fruitful theory to explain “normative latitudes” and the behaviour accruing to them. One of the particularities of these works stresses the importance of linking the normative aspects with speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 43 publications
1
29
0
2
Order By: Relevance
“…10 Nos propos ne sont pas sans rappeler les travaux sur la conditionnalité de la règle qui ont été développés en lien avec la théorie des représentations sociales d'Abric [18] et Flament [19]. Ainsi, selon Gaymard [20], toute prescription comporte, au niveau même de la représentation qu'en ont les individus, des variations conditionnelles tolérables dites « transgressions légitimes » qui ne remettent pas en question la règle, mais rendent acceptable sa transgression dans un certain nombre de contextes. 11 Le risque fait partie inhérente de la vie et c'est un droit qui est d'ailleurs consigné dans la charte des droits et libertés de la personne âgée dépendante (« la personne âgée en perte d'autonomie garde la liberté de choisir son mode de vie (.…”
Section: Resultsunclassified
“…10 Nos propos ne sont pas sans rappeler les travaux sur la conditionnalité de la règle qui ont été développés en lien avec la théorie des représentations sociales d'Abric [18] et Flament [19]. Ainsi, selon Gaymard [20], toute prescription comporte, au niveau même de la représentation qu'en ont les individus, des variations conditionnelles tolérables dites « transgressions légitimes » qui ne remettent pas en question la règle, mais rendent acceptable sa transgression dans un certain nombre de contextes. 11 Le risque fait partie inhérente de la vie et c'est un droit qui est d'ailleurs consigné dans la charte des droits et libertés de la personne âgée dépendante (« la personne âgée en perte d'autonomie garde la liberté de choisir son mode de vie (.…”
Section: Resultsunclassified
“…Within this framework, we specifically focus on the theory of the central core (Abric, , , , , ; Flament, , , , , ; Gaymard, , , ; Guimelli, , ). This theory has been developed during the last 40 years.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Within this framework, we specifically focus on the theory of the central core (Abric, 1976(Abric, , 1994(Abric, , 2001a(Abric, , 2001b(Abric, , 2003Flament, 1984Flament, , 1987Flament, , 1991Flament, , 1994aFlament, , 1999Gaymard, 2003Gaymard, , 2006Gaymard, , 2014Guimelli, 1993Guimelli, , 1998. This theory has been developed during the last 40 years.…”
Section: The Theory Of the Central Core Of Social Representationsmentioning
confidence: 99%
“…The social representation of new technologies, specifically nanotechnology, is a new field for the construction of legal expertise knowing that the conditionality theory has revealed that social norms could cause legal norms to evolve (Gaymard, 2014). For a long time the law has constituted an area of knowledge in which theory and practice are separated, thus presenting difficulties in its approach to them.…”
Section: Introductionmentioning
confidence: 99%
“…The structural approach defends the existence of a central core representing the collective part of the representation, and a periphery that would appear to be linked more with individual practices. Although interesting to describe the configuration of the social representation, this model nevertheless has limits when the normative aspects of the representation are addressed (Gaymard, 2014). At the moment we can ask ourselves how nanotechnology is integrated into common sense (to what degree?…”
Section: Introductionmentioning
confidence: 99%